The impact of digital advertising on the intention to donate to muslim NGOs through crowdfunding. - Abduhu , Salem; Jan , Muhammad Tahir (International Journal of Accounting, Finance and Business, 2024)
This article explores the impact of digital advertising on the intention to donate into Muslim NGOs that employ crowdfunding platforms. Crowdfunding has become an increasingly popular method for collecting funds for a specific program or campaign. It empowered many smaller entrepreneurs and charitable organizations as it provides them with a bigger pool of potential donators that they could approach through the use of crowdfunding platforms. Muslim NGOs started to rely on crowdfunding platforms as most of the time they are unable to fully sustain themselves and rely on donations to support their activities. As crowdfunding became more popular, more similar campaigns were created which made it harder for many NGOs to collect enough funds for their campaigns. Digital advertising made it easier and simpler to advertise products and services. It has become an essential part of how many companies operate in the digital world. In this review of the literature, we examine the factors that affect donors’ intention to donate to crowdfunding platforms. This article provides a thorough analysis of the literature with a particular emphasis on digital advertising and crowdsourcing of Muslim NGO. The study examines the junction of these two domains by synthesizing findings from previous research articles and other pertinent literature. By utilizing digital advertising, NGOs can promote their activities as well as motivate potential donators into donating to their crowdfunding campaigns.